Desenvolvimento de um protótipo para alimentação de pós para aspersão térmica em tocha de plasma - Souza, Eraldo Câmara de (2010)
The nanometric powders have special features that usually result in new properties, originating applications or expanding them in various fields of knowledge. Because having a high area/volume ratio, phenomena such as superficial strength of adsorption becomes greater than the weight of the powder which makes more difficult its handling. The high power of agglomeration of these powders requires study and development of equipments to enable its management into the plasma torch. The objective of this work is to develop a powder feeder which can solve the mainly problems about insertion of powder into the thermal spray developed in the laboratory of plasmas, which are carried out with plasma torch arc not transferred (plasma spray). Therefore, it was made a aluminum s powder feeder and tests were performed to verify their operation and determine its rate of deposition by spraying powders of niobium pentoxide (Nb2O5) and titanium dioxide (TiO2) with particle sizes less than 250 mesh (<0.063 mm). We used masses of 0.5 g - 1.0 g and 1.5 g of each powder in tests lasting 15 seconds - 20 to 25 seconds for each mass. The tests were performed in two ways: at atmospheric pressure using argon gas with a flow of 9 l / min as carrier gas and through a Venturi pipe also using argon gas with a flow of 9 l / min as carrier gas and with a flow of 20 l/min as the feed gas passing through the Venturi pipe. The powder feeder developed in this paper is very easy to be handling and building, resulting in feeding rate of 0.25 cm3/min - 1.37 cm3/min. The TiO2 showed higher feeding rates than the Nb2O5 in all tests, and the best rates were obtained with tests using mass 1.5 g and time of 15 seconds, reaching feeding rate of 1.37 cm3/min. The flow of feed had low interference in feeding rate during the tests